Retired But Not Tired: Insights for Global Application from Skill Acquisition among Retirees in Nigeria - Feranmi Oluwagbemileke; Mary Yemisi Falana; Sefunmi Winifred Ayo-Akindoju (Journal of Child, Family, and Consumer Studies, 2025)
Retirement presents economic, social, and psychological challenges, particularly in regions with weak social welfare systems. It is therefore necessary to identify practical strategies that ensure sustainable post-employment living.This study examines the role of skill acquisition in promoting sustainable living among retirees in Ondo West Local Government Area, Nigeria. A descriptive survey research design was employed, with data collected from 38 purposively selected retirees through a structured questionnaire comprising 40 items. The instrument contained sections on demographic characteristics, engagement in skill acquisition, perceived benefits and barriers, and strategies for enhancement. Descriptive and inferential statistics, including mean, variance, and t-tests, were used for analysis. Findings reveal that retirees recognize skill acquisition as a viable strategy for ensuring financial independence, social engagement, and personal fulfillment, with notable gender differences in skill preferences. However, barriers such as financial constraints, lack of awareness, and insufficient institutional support were identified. The study recommends early pre-retirement training, increased financial support, and community-driven interventions to enhance retirees’ economic stability. Although localized in Ondo West, the study provides insights with wider relevance for sustainable retirement planning in developing economies